STRATEGI KETERPILIHAN CALEG ETNIS TIONGHOA PADA PEMILU LEGISLATIF DI KOTA MEDAN - Nahdiah, Afidatun -; Permana, Panji Anugrah (FISIP Universitas Malikussaleh, 2024)
The purpose of this study was to explain the cause of ethnic Chinese legislative candidates Sofyan Tan gained superior votes and survived with the basis of the majority of indigenous voters. Sofyan Tan's election is analyzed using patronage theory, namely how patronage variations are used and affect the process of selecting Sofyan Tan. The study uses qualitative methods, with data collection techniques namely observation and interviews. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results showed that the succession strategy of candidates for legislative members from the Chinese minority ethnicity was to use patronage in the form of long and sustainable social education assistance so that he succeeded Cash or goods that are only given once ahead of the election, but assistance in the social field of education that is long and sustainable, and has begun to be distributed long before the election stage. The social assistance of education provided by Sofyan Tan can be classified into several forms, which is the source of Sofyan Tan's victory.